Smart objects: come il digitale organizza la nostra vita - Emanuele Crescimanno (2018)
Computer, tablet, smartphone are the most important everyday objects in our life because we made experiences by them; they run due to their software: so it is necessary to understand it, his form, his design and his tradeoffs to understand the role of these objects and the possibilities of a conscious use of them.